Associação entre hábitos bucais de sucção não nutritivos, o trespasse vertical e a relação transversal entre os arcos dentários decíduos, em nipo-brasileiros - Sato, Vivianne Da Cunha Barbosa (2006)
This study aimed at evaluating the association between nonnutritive sucking habits and anterior openbite and posterior crossbite malocclusions, in Japanese-Brazilian children in the deciduous dentition. For this reason, one previously calibrated dentist examined 410 children, 206 males and 204 females, with ages varying between 2 and 6 years, from private primary educations schools in São Paulo state. Survey questionnaires regarding sucking habits history were send to child parents. Qui-square test (p<0.05) were used to verify the association between habits and the prevalence of the malocclusions evaluated. Additionally, stepwise logistic regression was used to obtain the odds ratio. The prevalences found in the sample for sucking habits, anterior openbite and posterior crossbite were 44.6%, 4.4% and 4.4%, respectively. There was statistical significant association between anterior openbite and sucking habits history (O.R.=10.77), habit persistency from 2 to 4 years of age (O. R.=22.06) and habit persistency from 4 to 6 years of age (O. R.=17.31). Additionally, significant association between posterior crossbite and habit persistency from 2 to 4 years of age (O.R.=4.02) was observed. Considering the habit interruption time, the results showed that the group which had interrupted the sucking habits for 6 months or less displayed higher prevalence of anterior openbite and posterior crossbite in comparison to the control group and to the group of children who had interrupted the habit for more than 6 months. It was concluded that sucking habits represent important etiological factors of anterior openbite and posterior crossbite in Japanese-Brazilians children.